Assessment of Triglycerides Levels in Gestational Diabetes - A cross-sectional study - Mumtaz Jahan, Hira Sulaman, Naila Qazi, Uzma Manzoor, Sajida Asghar, Madiha Shaheen (Journal of Rawalpindi Medical College, 2021)
Introduction: Gestational diabetes mellitus (GDM) is the impaired glucose tolerance that is recognized first time during pregnancy. When a woman gets pregnant, glucose intolerance increases and manifests as a positive GDM diagnosis. It has been considered a transient condition because after delivery the majority of cases return to normoglycemic levels. Materials and Methods: This cross-sectional study was conducted in the Department of Obstetrics and Gynecology, Rawal Institute of Health Sciences, Islamabad. Data were collected in a period of 06 months between July 2020 to January 2021. A total of 100 women were included in the study and 5cc of their blood was taken from the vein under aseptic measures for measuring serum triglyceride levels after 12 hours of overnight fasting. Data were analyzed in SPSS version 20.0. Results: The overall mean Serum Triglyceride level of study subjects was 181.17±33.62 mg/dl, with a range of 151-359 mg/dl. Around two-third, 66% of women had <181 mg/dl of Serum Triglyceride level, and 34% of patients had it >181 mg/dl. Our observation was that the mean level of Serum Triglyceride was not different significantly among age, BMI, gestational age, educational and socio-economic groups with p-value >0.05. Conclusion: This study highlights that the circulating mean triglyceride level in GDM subjects was significantly elevated from the normal pregnancy levels.